(untitled) (Asian Education Studies, 2017)
This article discusses the qualifying function of the education of the young and adults (EJA) and work, as a humanizing source of wealth and welfare, which differs from the perspective of education throughout life. It is grounded on the critical sociological approach, being DELINEADO with a study of critical revision using documental and bibliographic researches and with a qualitative analysis of the information. It concludes that the educational policies in Brazil are markedly influenced by the determinations from UNESCO, responsible for the diffusion of the perspective of lifelong learning, subsumed to the requirements of the job market and to the social role that is meant for each individual and which differs from the qualifying function of EJA and work. As a political-pedagogical implication of this statement, it is noted that the worker-work relationship is socially determined and that EJA cannot ignore this reality, given that the knowledge of the mechanisms of exploration will make possible and clarify the human emancipation of the worker.